Mechanism for microwave pulse shortening in a relativistic BWT; Technical Physics Letters; Vol. 25, iss. 3 - Korovin S. D. Sergei Dmitrievich; Mesyats G. A. Gennady Andreyevich; Pegel I. V. Igor Valerievich; Polevin S. D.; Tarakanov V. P. Vladimir Pavlovich (1999, 1999)
Title screen